2011
DOI: 10.1073/pnas.1018456108
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial divergence and ongoing adaptation via the hedgehog pathway

Abstract: Adaptive variation in craniofacial structure contributes to resource specialization and speciation, but the genetic loci that underlie craniofacial adaptation remain unknown. Here we show that alleles of the hedgehog pathway receptor Patched1 (Ptch1) gene are responsible for adaptive variation in the shape of the lower jaw both within and among genera of Lake Malawi cichlid fish. The evolutionarily derived allele of Ptch1 reduces the length of the retroarticular (RA) process of the lower jaw, a change predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
148
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(161 citation statements)
references
References 51 publications
(63 reference statements)
8
148
0
Order By: Relevance
“…The results of this experiment were consistent with our previous work (Fig. 3): cyclopamine-treated LF larvae developed shorter RAs whereas the length of the mandible remained essentially unaffected (10). We also found that treated LF larvae exhibited IOP width/length ratios that were statistically indistinguishable from those of MZ (Fig.…”
Section: Chemical Manipulation Of the Hh Signaling Pathway Recapitulatessupporting
confidence: 82%
See 4 more Smart Citations
“…The results of this experiment were consistent with our previous work (Fig. 3): cyclopamine-treated LF larvae developed shorter RAs whereas the length of the mandible remained essentially unaffected (10). We also found that treated LF larvae exhibited IOP width/length ratios that were statistically indistinguishable from those of MZ (Fig.…”
Section: Chemical Manipulation Of the Hh Signaling Pathway Recapitulatessupporting
confidence: 82%
“…The QTL peak was located squarely over the ptch1 locus (i.e., LOD peak of 6.25 at 25 cM, 95% CI, 18-42 cM). Although the CI associated with the QTL peak is large, our previous work has demonstrated, via association mapping among natural cichlid populations, that variation in jaw morphology is associated with a relatively narrow ∼10-kb genomic region located ∼15 kb upstream of the first ptch1 exon (10). As expected, the allelic effects of the IOP QTL on LG12 were consistent with the interspecific variation observed between parental species: inheritance of the ancestral (i.e., LF) ptch1 allele was associated with the development of a relatively wider and shorter IOP, whereas the derived (i.e., MZ) allele was associated with a relatively narrower and longer IOP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations